PENGARUH GAYA KEPEMIMPINAN DAN LOYALITAS TERHADAP KINERJA KARYAWAN PT. LAPI LABORATORIES - Fatari Fatari; Rani Sri Sumarsih; Gatot Hartoko (National Conference on Applied Business, Education, & Technology (NCABET), 2022)
This study aims to determine the effect of Leadership Style on Performance, the influence of Loyalty on Performance and determine the influence of Leadership Style and Loyalty simultaneously on the performance of employees of PT. LAPI Laboratories. The research method used is quantitative associative. The population in this study were 75 employees and using a non-probability sampling method, namely the saturated sample, the sample obtained was 75 respondents. The results showed that leadership style had no effect on performance, it could be seen from the calculation of tcount = 0.909 <ttable = 1.666. Loyalty has a significant effect, it can be seen from the calculation of tcount = 2,594 > ttable = 1,666. Leadership Style and Loyalty have a simultaneous effect on performance as shown by the results of the calculation Fcount > Ftable, namely 3.809 > 2.16. The coefficient of determination (R Square) is 0.096, this means that the variables of Leadership Style and Loyalty affect 9.6% of performance. The conclusion is that there is a simultaneous influence of Leadership Style and Loyalty on the performance of employees of PT. LAPI Laboratories